Postoperative Pain Following Multi-Visit Root Canal Treatment of Teeth with Vital and Non-Vital Pulps (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Post-obturation pain is one of the primary problems following root canal treatment. Although in most cases pain does not last long, but could be a source of embarrassment to the dentist and annoying for the patient.Objectives: This prospective study was conducted to assess the incidence of postoperative pain after multivisit root canal treatment of teeth with vital and nonvital pulps.Methods: Total, 52 patients with teeth requiring endodontic treatment were identified and included in this study. The patients were randomly assigned and treated in a military hospital and in government dental college hospital into two groups. The teeth of patients in group 1 were with vital inflamed pulp; group 2 were with non-vital pulp with or without periapical radiolucency (0-5mm). Patients were treated in multiple visit procedure. They were asked whether they experienced any postoperative pain to rate the level of discomfort as no, mild, moderate, or severe pain. Data were analyzed statistically using the chi-square test.Results: No significant difference in postoperative pain was found between vital and non-vital pulps (p=0.2). Mild and moderate pain occurred in 4.34% and 4.34% respectively in teeth with vital pulp and 17.3% and 3.44% in teeth with non-vital pulp respectively. There was no significant difference in postoperative pain between the two groups (p>0.05).Conclusions: The incidence of postoperative pain did not differ between vital and non-vital teeth.Key words: Postoperative dental pain; root canal treatment; vital and non-vital pulp DOI: 10.3329/jafmc.v6i2.7271JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.28-31